The Impact of Online Information Chaos on the Credibility of Social Networks: A field Study on a Sample of the public of Social Network - Suleiman, Amira Ahmed (Journal of Humanities & Social Sciences, 2019)
The study seeks to study the chaos of information on social networks, their impact on the credibility of these networks, the identification of forms of information chaos in the social networks, the degree of public confidence in the information they deal with, their sense of information chaos, Through social networking sites. The study was conducted on (378) individual subscribers of different social networks, "Facebook and LinkedIn and Twitter." Results: One of the most important findings of the study is that more than half of the sample of the study feel the chaos of information on social networks, due to the large number of accounts on the networks and the increase of anonymous information, as well as the lack of control over the information published on those networks. There are also many forms of information chaos on social networks: anonymous information, privacy violations, infringement of intellectual property rights and rights of publishers, the proliferation of counterfeit and contradictory information, the manufacture and dissemination of viruses, breaches and disruption of devices, and multiple personal or institutional accounts.The researcher recommends the need to pay attention to the enactment of media legislation and laws related to the new media environment for social networking sites to reduce the chaos of information and privacy protection, and to raise awareness of the importance of social networking sites and the Publishing Standards through courses and workshops to reduce the chaos.
Keywords: information chaos; social networks; credibility; censorship